ESD protection for negative charge pump (CP) using CP internal switches. (February 2016) - Srivastava, Ankit; Worley, Gene; Quan, Xiaohong; Miao, Guoqing
Abstract: The standard ESD protection schemes are not very reliable for negative charge pump used in Class G power amplifiers. This work presents a novel ESD protection scheme using internal charge pump switches as ESD clamps. Transmission line pulsing (TLP) measurements show that an elevated level of ESD protection can be achieved with this scheme. Graphical abstract: The core idea of the new scheme using CP internal switches as ESD clamps. Highlights: The standard ESD schemes are not very reliable for negative charge pumps (CPs). Ballasting on CP switches adds to significant silicon area. Using CP internal switches as ESD clamps provides robust protection. Simple trigger circuits can be used to enable the clamps. TLP measurements show that the pin can handle > 18 A, 100 ns TLP pulses.